2019
DOI: 10.1093/occmed/kqz023
|View full text |Cite
|
Sign up to set email alerts
|

Healthy workers or less healthy leavers? Mortality in military veterans

Abstract: Background: The 'healthy worker effect' predicts that longer employment is positively associated with reduced mortality, but few studies have examined mortality in military veterans irrespective of exposure to conflict. Aims: To examine mortality in a large national cohort of Scottish veterans by length of service. Methods: Retrospective cohort study comparing survival in up to 30 years follow-up among 57,000 veterans and 173,000 people with no record of service, matched for age, sex and area of residence, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…However the 'healthy worker effect' is also likely to have contributed to explaining the better outcomes in longer-serving veterans; we have shown elsewhere that this is an important factor in veterans. 16 The association with lung cancer is unsurprising in view of the shared risk factor of smoking, and the increased risk with comorbid mental health conditions is also consistent with known associations between smoking and mental ill-health. [17][18][19] A longitudinal cohort study of Open access UK military personnel spanning the period 2004-2009 demonstrated a fall in overall smoking prevalence from 25% to 21%, and of those who initiated smoking during the study period, there was an association with both newonset psychological distress and remission of symptoms, and also with having been deployed.…”
Section: Discussionmentioning
confidence: 76%
“…However the 'healthy worker effect' is also likely to have contributed to explaining the better outcomes in longer-serving veterans; we have shown elsewhere that this is an important factor in veterans. 16 The association with lung cancer is unsurprising in view of the shared risk factor of smoking, and the increased risk with comorbid mental health conditions is also consistent with known associations between smoking and mental ill-health. [17][18][19] A longitudinal cohort study of Open access UK military personnel spanning the period 2004-2009 demonstrated a fall in overall smoking prevalence from 25% to 21%, and of those who initiated smoking during the study period, there was an association with both newonset psychological distress and remission of symptoms, and also with having been deployed.…”
Section: Discussionmentioning
confidence: 76%
“…Consistent with another study of the association of smoking with non-survival at work 23 , we now supplement this notation with a similar effect at the high-altitude mine. Furthermore, in a large 30-year cohort observation of veterans, they demonstrated that smoking-related diseases contributed most in mortality of those who left prematurely 24 . Taken together, we conclude that smoking is an important modifiable risk factor for early work leave; therefore, persistent advice on smoking cessation for mine employees at high altitude should be supported by the management and not ignored by the medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Bergman et al 34 Quantitative 56 206 Veterans Retrospective, 30-year cohort study of 56 206 veterans, examined the association between previous selfharm and suicide, data retrieved from Scottish Health Records Examined data on 266 vets. Fifty (18%) had a previous history of self-harm.…”
Section: Methods Of Suicidementioning
confidence: 99%
“…Bergman et al 34 found that 18% of veterans who died by suicide had a previous history of self-harm. These associations were lower in younger veterans under the age of 30 and higher in older veterans over the age of 50.…”
Section: Mh and Self-harmmentioning
confidence: 99%